The unkindness of ravens [large type] - Hilliard, M. E. (A Greer Hogan mystery, 2022)
"Librarian Greer Hogan matches wits with a deviously clever killer in M.E. Hilliard's chilling series debut, ideal for fans of Louise Penny and Dorothy L. Sayers. Greer Hogan is a librarian and an avid reader of murder mysteries. She also has a habit of stumbling upon murdered bodies. The first was her husband's, and the tragic loss led Greer to leave New York behind for a new start in the Village of Raven Hill. But her new home becomes less idyllic when she discovers her best friend sprawled dead on the floor of the library. Was her friend's demise related to two other deaths that the police deemed accidental? Do the residents of this insular village hold dark secrets about another murder, decades ago? Does a serial killer haunt Raven Hill? As the body count rises, Greer's anxious musings take a darker turn when she uncovers unexpected and distressing information about her own husband's death...and the man who went to prison for his murder . She is racked with guilt at the possibility that her testimony may have helped to convict an innocent man. Though Greer admires the masters of deduction she reads about in books, she never expected to have to solve a mystery herself. Fortunately, she possesses a quick wit and a librarian's natural resourcefulness. But will that be enough to protect her from a brilliant, diabolical murderer? And even if Greer manages to catch the Raven Hill killer, will living with her conscience prove a fate worse than death? ("--